Psychosocial risks and quality of life in primary care workers: integrative review - Valencia-Contrera, Miguel (Universidad de Sonora, 2022)
Introduction: Workers are exposed to a complex variety of health and safety hazards, standing out psychosocial risks, which in multiple studies has evidenced that account for their presence and their impact on quality of life of health workers at hospital level. However, there are few approaches at the primary care level, especially in times of the COVID-19 pandemic. Objective: Analyze the status in the latest advances, the presence of psychosocial risks and how they impact the quality of life of health workers in primary health care, before and after the COVID-19 pandemic. Methodology: This integrative review was based on Crossetti's five stages. A question was raised that guided the searches carried out, using DeCS and Boolean AND descriptors; WOS, PUBMED, BVS and SCIELO databases were consulted, from the year 2015 to 2020, where articles in Spanish, English and Portuguese were included, these related to primary health care and psychosocial risks. The quality criteria of the articles were analyzed, and the sample was comprised by 8 articles. Results: From the articles, 38% were from Latin America and 50% were carried out in 2020. The majority identified work stress as the main risk. It was reported that the most affected group was nursing in 88%. Quality of life had a negative relationship in the presence of psychosocial risks. Conclusions: The articles show the presence of psychosocial risks in primary care workers, which negatively impact their quality of life.